Plant mycorrhizal status, but not type, shifts with latitude and elevation in Europe. Issue 6 (31st March 2017) - Bueno, C. Guillermo; Moora, Mari; Gerz, Maret; Davison, John; Öpik, Maarja; Pärtel, Meelis; Helm, Aveliina; Ronk, Argo; Kühn, Ingolf; Zobel, Martin
Abstract: Aim: Identifying the factors that drive large‐scale patterns of biotic interaction is fundamental for understanding how communities respond to changing environmental conditions. Mycorrhizal symbiosis is a key interaction between fungi and most vascular plants. Whether plants are obligately (OM) or facultatively (FM) mycorrhizal, and which mycorrhizal type they form – arbuscular mycorrhizal (AM), ectomycorrhizal (ECM), ericoid mycorrhizal (ERM) or non‐mycorrhizal (NM) – can have strong implications for plant species distribution at the continental scale and on the responses of plants to environmental gradients. Location: Europe, north of 43° latitude and excluding Russia, Belarus and Moldova. Time period: Undefined. Major taxa studied: Vascular plants. Methods: Using published sources, we compiled the most complete dataset yet of plant mycorrhizal and geographical information for Europe, comprising 1442 plant species. We mapped the European distributions of plant mycorrhizal status (OM and FM) and type (AM, ECM, ERM and NM) and analysed their relationships with climatic, edaphic and plant productivity drivers on a 50 km × 50 km equal‐area grid. Results: The distribution of mycorrhizal types in Europe was driven by mean temperature, soil pH and productivity. AM plant species predominated throughout the region, but at higher latitudes the share of NM and, to a lesser extent, ECM and ERM species increased. FM species predominated over OM species, and this increased with latitude and was dependent on temperature drivers. The high share of OM species in the central European mountains indicates a possible influence of historical glacial refugia. Main conclusions: Our results challenge the prevailing view of parallel trends in the latitudinal and elevational distribution of mycorrhizal types and demonstrate distinctive responses of plants with different mycorrhizal status to climatic, edaphic and biogeographical drivers at the European scale.